Numero de dias de ocorrencia de orvalho em Botucatu, SP. - Tubelis, A. (My University, 1985)
This paper analyses the dew occurrence in Botucatu, Sao Paulo State, Brazil, in the period from 1971 to 1984. The phenomenon was observed on the grass plot of the Climatological Station in the 'Presidente Medici' Experimental Farm. The station is installed on soil 'Terra Roxa Estruturada', on a middle slope, declivity of 8% and east exposure. Days with dew were summed for the following periods: month, year, season, no rainy period and rainy period. For each period the following values were calculated: mean, mean standard errors and mean confidence interval. Also the absolute extreme values and the amplitude of variation were determined. The confidence interval of the mean were calculated by the 't' statistic, at the level of 5% of error probability. The means were compared by using the 't' statistic, at the level of 5% of error probability. The following table of values corresponds to the regime of dew occurrence in Botucatu, expressed in number of days with dew. The dew occurrence regime in Botucatu was analysed comparatively with the regime at Itatinga, in Sao Paulo State and with the regime of Rio Grande, in Rio Grande do Sul State. -English summary
Number of days of dew occurrence in Botucatu, SP, Brazil
Keywords: dew; microclimatology; precipitation